2016
DOI: 10.21747/2183-9077/rapla6
|View full text |Cite
|
Sign up to set email alerts
|

Variação entoacional no Português do Brasil: uma análise fonológica do contorno nuclear em enunciados declarativos e interrogativos

Abstract: In this paper we present a phonological analysis of the nuclear contour of declarative and interrogative utterances in Brazilian Portuguese, as spoken in 7 regions, along the Atlantic Coast -Paraíba, Sergipe, Bahia (North); Minas Gerais, Rio de Janeiro (Center), Santa Catarina and Rio Grande do Sul (South). Declaratives present a falling contour, with phonetic differences across varieties. As for interrogatives, more variation was found. Namely, two types of nuclear contours were observed: a rising contour in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 8 publications
0
5
0
1
Order By: Relevance
“…Six dialectal varieties of Portuguese are of interest for this study: Standard European Portuguese (SEP), Maputo Mozambique Portuguese (MMP), Northeastern Brazilian Portuguese (NEBP), Rio de Janeiro Portuguese (RJBP), São Paulo Brazilian Portuguese (SPBP), and Florianópolis Brazilian Portuguese (FLBP), with the latter three being considered Southern dialects of Brazilian Portuguese (see Castelo 2016;Nascentes 1953). One of the most widely studied interrogatives is the information-seeking or 'neutral' yes-no question which corresponds to a request for information without the expectation of a positive or negative answer and is characterised by the absence of focus on any of the words in the question (de Moraes 2008).…”
Section: Yes-no Interrogatives In Portuguesementioning
confidence: 99%
“…Six dialectal varieties of Portuguese are of interest for this study: Standard European Portuguese (SEP), Maputo Mozambique Portuguese (MMP), Northeastern Brazilian Portuguese (NEBP), Rio de Janeiro Portuguese (RJBP), São Paulo Brazilian Portuguese (SPBP), and Florianópolis Brazilian Portuguese (FLBP), with the latter three being considered Southern dialects of Brazilian Portuguese (see Castelo 2016;Nascentes 1953). One of the most widely studied interrogatives is the information-seeking or 'neutral' yes-no question which corresponds to a request for information without the expectation of a positive or negative answer and is characterised by the absence of focus on any of the words in the question (de Moraes 2008).…”
Section: Yes-no Interrogatives In Portuguesementioning
confidence: 99%
“…In EP, there are various nuclear contours in yes-no questions (such as H+L* LH%, L*+H H%, or H+L* L%), which appear to be distributed in a Castelo & Frota (to appear geographically non-contiguous way (Crespo-Sendra et al, 2014;Frota et al, 2015a). In BP, yes-no questions are characterized by a rising and risingfalling configuration in reading and semi-spontaneous speech (Silva, 2011;Castelo & Frota, 2015). In Northern varieties (Paraíba, Sergipe and Bahia), a rising nuclear contour is found (L*+H H% or L* H%), whereas Central and Southern varieties are characterized by a rising-falling contour (L*+H L%, in Rio de Janeiro and Minas Gerais; L* HL%, in Santa Catarina and Rio Grande do Sul), independently of the pragmatic meaning (Crespo-Sendra et al, 2014;Frota et al, 2015a;Frota et al, 2015b).…”
Section: Previous Studies On Intonational Variation In Portuguesementioning
confidence: 99%
“…The intonation of statements and yes-no questions was previously studied and thus the typical contours of these utterances for each region, when the text does not impose constraints on tune realization, have been independently established [8], [11], [14], [15], [16]. Examples of the complex tunes that characterize yes-no questions, in contrast with the simple fall found in neutral statements, are given in Figure 1 (capitals signal word stress).…”
Section: Speech Materialsmentioning
confidence: 99%
“…Previous work on the intonation of yes-no question in BP had shown that the complex rising-falling contour (L*+H L% or L* HL%) is a feature of Center and Southern varieties, whereas in Northern varieties a rising contour is predominant [15], [16]. We thus focused the analysis of tune-text accommodation in the regions with the complex tune (shown in Fig.…”
Section: Yes-no Questionsmentioning
confidence: 99%